Pengaruh Adopsi Teknologi PHSL (Pemupukan Hara Spesifik Lokasi) Berbasis Pertanian Presisi terhadap Pendapatan Petani Padi di Desa Jembungan, Kabupaten Boyolali, Jawa Tengah - Faiz Ridhan Faroka; Kudang Boro Seminar; Pudji Muljono (Institut Pertanian Bogor, 2013)
Abstract The highly increase of crop production in the future will be a compulsion and utilization of field will be more intensive. Therefore, precise pescription of crop fertilization is required. Site Specific Nutrient Management (SSNM) application is an innovative technology for rice farming through fertilization recommendation based on the principles of precision farming. The SSNM web-based application was developed by IRRI (International Rice Research Institute) in Philippines in collaboration with Agricultural Research & Development Council (LITBANG Pertanian) .The aim of this research is to study the impact, paritcularly on farmers’ income, in utilizing web-based version of SSNM. There was a significant differences in fertilization cost between the usage of SSNM-based farming system and manual-based farming system.. The manual based fertilization cost is Rp 23,078. (12.93 % of total cost) whereas the SSNM-based fertilization cost is Rp 320,065 ( 20.62% of total cost. The application of SSNM was able to increase average rice production about 314.38 kg / hectare and thus farmers income raised to Rp 1,100,328 / hectare. Keyword : site-specific fertilization, rice framing, rice production, SSNM, precision farming